Low Power Split Unit Air Conditioning using Thermal Energy Storage (TES) System - Herawan, Safarudin Gazali; M. Syamsul, Hadi; Shahrin, Omar; Nor Effyza, Roslan (2010)
Thermal energy storage (TES) systems store a sizeable quantity of “cool” thermal energy that helps meet the cooling load of a building. A typical system of TES consists of a large vessel filled with water or brine that may contain multiple small containers such as encapsulated bricks or balls, that filled with a fluid. TES system can save energy in several ways, compared to conventional chillers. Nighttime chillers operation takes advantage of lower dry-bulb temperatures (for air-cooled condensers) or moderately lower wet-bulb (for water-cooled condenser) temperatures relative to daytime values, which also reduce chiller to lift. Since the thermal energy system has a great benefit for saving the energy, it is very interesting to adopt this system into the split unit air conditioning for getting a low power consumption. It is found that the electrical consumption of this system can reduce up to 70% by comparing to conventional split unit air conditioning with the same capacity. The Coefficient of Performance (COP) of this system is almost twice higher than the conventional one, which is in a range of 5.491 – 5.89 as 3.05 – 3.24 for conventional split unit.